Invasive salmonellosis in paediatric patients in the Northern Territory, Australia, 2005–2015. (13th April 2021) - Hamilton, Natasha J; Draper, Anthony D K; Baird, Rob; Wilson, Angela; Ford, Tim; Francis, Joshua R
Abstract : Aim: To describe the epidemiology of invasive Salmonella disease in children in the Northern Territory, Australia. Methods: Design: A retrospective review of invasive salmonellosis cases identified by pathology records and the Northern Territory Notifiable Disease Surveillance System. Case definitions: Those aged 18 years or under, with Salmonella cultured from a usually sterile site, collected in the Northern Territory between 1 July 2005 and 30 June 2015. Outcome measures: The primary outcome measure was the annual incidence rate of invasive salmonellosis, comparing rates between Indigenous and non‐Indigenous children. Results: There were 86 cases of invasive Salmonella infection in children over the 10‐year period; an annual incidence of 14.1 per 100 000 population, in those aged less than 18 years. Gastrointestinal Salmonella notifications were similar between Indigenous and non‐Indigenous children. In children aged less than 15 years, the rate of invasive salmonellosis was higher in Indigenous children compared to non‐Indigenous children (23.4 per 100 000 compared with 11.6 per 100 000); rate ratio 2.0 (95% confidence interval 1.3–3.3, P = 0.002). Indigenous children with invasive salmonellosis had a median hospital stay of 8 days, which was compared to 5 days for non‐Indigenous children ( P = 0.015). The highest incidence rate of invasive salmonellosis occurred in Indigenous patients less than 12 months of age (138 per 100 000). Conclusion: The Northern Territory of Australia has high rates of invasive salmonellosis in children. Indigenous and non‐Indigenous children experience similar rates of Salmonella gastroenteritis but Indigenous children experience higher rates of invasive salmonellosis.